Cross - cultural adaptation and preliminary validation of the Turkish version of the Early Childhood Oral Health Impact Scale among 5-6-year-old children - UYSAL, ÖMER; Peker, Kadriye; Uysal, Omer; Bermek, Gulcin (My University, 2011)
Background: In Turkey, formal pre-primary education for children 5-6 years old provides the ideal setting for school-based oral health promotion programs and oral health care services. To develop effective oral health promotion programs, there is a need to assess this target group-s subjective oral health needs as well as clinical needs. The Early Childhood Oral Health Impact Scale (ECOHIS) is a well-known instrument for assessing oral health quality of life in children aged 0-5 years old and their families. This study aimed to adapt the ECOHIS for children 5-6 years old in a Turkish-speaking community and to undertake a preliminary investigation of its psychometric properties.
Keywords: oral health